Insights Into Neuroimaging Findings of Patients With Coronavirus Disease 2019 Presenting With Neurological Manifestations - Chen, Boran; Chen, Chaoyue; Zheng, Junkai; Li, Ruoyu; Xu, Jianguo (Frontiers in Neurology, 2020)
Objective: This mini review aims to provide insight into the neurological imaging in patients with coronavirus disease 2019 (COVID-19). Methods: PubMed, EmBase and Web of Science were searched through July 21, 2020 for relevant studies reporting the neuroimaging findings in COVID-19 patients with neurological manifestations. Proportion estimate with a 95% confidence interval (CI) were pooled after the Freeman-Turkey transformation. The heterogeneity across the included studies was also assessed. Results: Overall, 11 studies with a total of 659 patients were included. The pooled proportion estimate of abnormal neuroimaging finding in patients who exhibited neurological manifestation and underwent brain CT or MRI was 59% (95%CI, 39%-77%). The proportion of acute/subacute ischemic infarction, intracranial hemorrhage, subcortical or deep white matter abnormalities were 22% (95% CI, 17%-28%), 24% (95%CI, 17%-30%), 27%(95%CI, 12%-45%), respectively. Conclusion: This mini review comprehensively detailed neuroimaging findings of patients with COVID-19 and neurological manifestations. Clinicians should be familiar with the neuroimaging patterns to catch the sight of brain abnormalities caused by SARS-CoV-2.